Interlaced viscoelastic damping treatments with tridimensional distribution - Matos, Francisca Maria Morais de (2021)
Viscoelastic damping treatments, as passive damping control mechanism, have a wide application due to their high efficiency and reduced structural modification. The strong frequency and temperature dependency of these material’s properties, and the representation of the deformation pattern developed in the dissipative layer are key elements to the numerical simulation of such damping treatments. Free layer damping configurations provide a simple solution, but despite being characterized by an expeditious and simple application procedure, its efficiency is comparatively reduced and therefore are usually disregarded as valid solutions for critical structures. To increase the efficiency of these damping treatments, while maintaining the advantages of an application procedure based on a simple deposition of a single layer of material on the structure surface, a new configuration – Interlaced damping layer – is herein proposed and assessed. This new configuration takes advantage of the shear effect and border effect provided by a three-dimensional interlaced layering scheme combining one or several materials. The numerical and experimental results demonstrate the feasibility of this proposed and promising configuration, that can provide a valid replacement for constrained damping layers, which often require a time consume and laborious placement procedures, and in some cases, such those where the target component has a complex geometry, is even impracticable or severely damaged during the application.